Immunological efficiency of Haemophilus influenzae type b polyribosyl ribitol phosphate combined with detoxified lipooligosaccharide in a rabbit model - Amin Arsang; Seyed Davar Siadat; Masoumeh Saberpour; Farshad Nojoomi (Iranian Journal of Microbiology)
Background and Objectives: Haemophilus influenzae type b (Hib) could cause severe life-threatening infections in children. Combine vaccines have reduced invasive diseases, but disease management is still necessary. The aim of this research was to evaluate the immunological efficiency of polyribosyl-ribitol-phosphate combined with detoxified lipooligosaccharide (PRP-dLOS) in a rabbit model. Materials and Methods: PRP purification, LOS extraction, and endotoxin evaluation were performed using modified CY medium, hot phenol, and limulus amebocyte lysate methods, respectively. Rabbit groups were immunized with PRP (10 µg), dLOS (20 µg), and PRP-dLOS combine (10 µg+20 µg) three times on days 0, 14, and 28. Serum samples were acquired on days 0, 14, and 28 post-immunization, then IgM and IgG levels were assayed by enzyme-linked immunosorbent assay. Results: The concentrations of PRP, dLOS, and endotoxin were 1160 mg/L, 440 μg/mL, and 1450 EU/mL, respectively. PRP-dLOS combine led to a significant increase in IgG and IgM levels on days 14 and 28 post-immunization. After immunization with PRP-dLOS combine, serum levels of IgM and IgG increased from 16.8 to 29.3 µg/mL and 29.8 to 61.4 µg/mL, respectively from day 14 to day 28. Conclusion: PRP-dLOS combine is a promising approach for Hib management without the fear of delay in immune responses and interference with other vaccines.